Optimization of Digital Business Communication for MSMEs: Strategies to Build Brand and Customer Loyalty - Lunarindiah, Gatri; Rahayu, Fatik; Sumiyarti, Sumiyarti; Puspitasari, Windhy; Ramadhanti, Mutiara (Pena Dimas: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are crucial contributors to Indonesia’s economy but continue to face barriers in adopting digital transformation, particularly in business communication, branding, and customer relationship management. Many MSME owners lack sufficient digital knowledge and confidence to implement effective online strategies, resulting in limited market visibility and customer engagement. To address these challenges, a community empowerment initiative was conducted with the primary goal of enhancing entrepreneurs’ digital competence and strengthening their ability to build brand identity and customer loyalty. The program applied the Participatory Action Research (PAR) approach, emphasizing collaborative involvement across stages of needs assessment, training, mentoring, and evaluation. Twenty MSME participants from the culinary, fashion, service, and household product sectors actively took part.  The results indicated significant improvements in understanding digital communication, developing creative content, and integrating social media into business strategies. Participants also demonstrated stronger collaboration, initiative, and confidence in digital marketing practices. These outcomes highlight the importance of hands-on, collaborative learning in bridging the digital literacy gap and fostering innovation among MSMEs. By improving their digital capabilities, MSMEs are better positioned to sustain growth, expand market reach, and contribute to a more inclusive digital economy. The initiative supports the United Nations Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) through continuous learning and skills development, SDG 8 (Decent Work and Economic Growth) through entrepreneurship empowerment, and SDG 9 (Industry, Innovation, and Infrastructure) by promoting innovation and sustainable digital transformation.